The use of immersive virtual reality technology in dementia care education for nursing students: A scoping review protocol - Joey Oi Yee Wong; Lillian Hung; Alison Phinney; Winnie Sun (PLoS ONE, 2026)
Objective This scoping review aims to identify and map the current available evidence regarding the use of immersive virtual reality technology in dementia care education for nursing students. Introduction With the growing population living with dementia, there is an urgent need to prepare nurses for quality dementia care through providing relevant dementia care education for nursing students. Virtual reality is an emerging education medium for nursing education and dementia care education for nursing students. However, little evidence focuses on mapping how immersive virtual reality technology has been used in dementia care education for nursing students. With the increasing development and use of this technology, it is crucial to explore current evidence regarding the content and learning outcomes, design and development, and implementation of immersive virtual reality technology in dementia care education for nursing students. Inclusion criteria Studies are eligible if they describe the use of immersive virtual reality technology in dementia education. The dementia care education must be designed for or targeted at nursing students or healthcare professional students (including nursing students) within academic settings, such as nursing schools, universities, and colleges. Methods The proposed scoping review will be conducted following the Joanna Briggs Institute methodology for scoping reviews and the Population, Concept and Context (PCC) framework. The review will search CINAHL, MEDLINE, PsycINFO, Scopus, Web of Science and ProQuest Dissertations and Theses Global. Grey literature search will be conducted via Google Scholar. Extracted data on authors, country, study design, setting, and findings relevant to the review objective will be presented in a data extraction table, accompanied by a quantitative summary of studies’ characteristics and narrative summary. The PRISMAS-ScR figure will detail the selection process. Review registration number This study has been registered with the Open Science Forum (OSF).